Avoiding Nightmare Forests : Insights From a Co-Creative Workshop - Nebasifu, Ayonghe; Ekström, Hanna ; 0000-0003-1793-1613; Iliev, Bogomil; Pihlainen, Sampo; Linser, Stefanie; Polo-Villanueva, Fredy D.; Viljanen, Anne; Charlier, Martin; Rahman, Md Rayhanur; Niedzialkowski, Krzysztof; Kuhlman, Juulia; Assmuth, Aino; et al. (Futures and Foresight Science, 2025)
Since the 1987 UN report “Our Common Future”, aimed at bridging divides among various stakeholders by advocating for “sustainable development”, renewed demands for environmentally adjusted measures have emerged, calling for a future that consolidates socially just, ecologically sound, and economically viable outcomes through sustainable forest management. For Nordic forests, this means policy measures focused on enhancing the forest-based bioeconomy, transitioning to a fossil-free society, adapting to climate change and combatting rapid biodiversity loss while securing continuous timber supply and valuable livelihoods. With expectations for Nordic forests to meet these demands, an impending challenge is how to bring about a desirable future while minimizing uncertainties. Given this urgency, we present a backcasting method applied to a co-creative workshop among research scholars to examine prospective scenarios for Nordic forests, ranging from nightmarish futures to risk-mitigation strategies. The workshop builds on an interdisciplinary research project to provide policy support for sustainable governance. We found that despite fears expressed about an adverse intensive forestry scenario, most participants identified multifunctionality and delivering multiple ecosystem services as critical to the future sustainability of Nordic forests. In addition, participants highlighted the coming need to incorporate hybrid forest management approaches for high-value biodiversity and to consider precautionary measures in forestry decisions. We conclude that approaching the future through a backcasting workshop promises to bring together a broad range of participants to create a common vision.
Publisher Copyright: © 2025 The Author(s). Futures & Foresight Science published by John Wiley & Sons Ltd.
Keywords: backcasting; bioeconomy; futures and foresight; interdisciplinary co-creation; Nordic forests and sustainability; risk-mitigation